The application of PGPR, Tricocompost, and MOL on the growth and quality of production, as well as the incidence of disease-causing agents in tomato plants in the Rurukan I district of Tomohon City - Denny Saroinsong; Maxi Lengkong; Noni N. Wanta (Britain International of Exact Sciences (BIoEx) Journal, 2025)
The objective of this research is to assess the impact of PGPR, Trichocompost, and MOL on the growth and quality of production, as well as the incidence of disease-causing microorganisms in tomato plants. This study will be conducted by comparing the use of beneficial organic microorganisms namely PGPR, Trichocompost, and MOL with inorganic farming systems that utilize synthetic fertilizers and manure as sources of nutrition for tomato plants. The research method employed a randomized block design consisting of three treatments as follows: Treatment A involved a combination of PGPR, Trichocompost, and MOL; Treatment B utilized inorganic fertilizers N, P, K along with foliar fertilizers Gandasil D and B; Treatment C consisted of chicken manure. Each treatment was replicated five times, with 50 plants per plot, resulting in a total of 750 plants for observation. The results indicated that the application of PGPR, Trichocompost, and MOL positively influenced the average flowering time, the average weight of 50 fruits, and the duration until fruit decay during the growth, development, and production phases of tomato plants. Furthermore, the use of PGPR, Trichocompost, and MOL effectively reduced the incidence of the fungal pathogen P. palmivora on leaves, the bacterial disease Erwinia sp. on leaves, and the fungal disease P. palmivora on fruit stems.